2005
DOI: 10.1371/journal.pbio.0030089
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Every Day: Abundant Recombination in a Virus during a Single Multi-Cellular Host Infection

Abstract: Viral recombination can dramatically impact evolution and epidemiology. In viruses, the recombination rate depends on the frequency of genetic exchange between different viral genomes within an infected host cell and on the frequency at which such co-infections occur. While the recombination rate has been recently evaluated in experimentally co-infected cell cultures for several viruses, direct quantification at the most biologically significant level, that of a host infection, is still lacking. This study fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 45 publications
3
86
2
1
Order By: Relevance
“…Using Cauliflower mosaic virus as a model, over 50% of viral genomes recovered after a single host infection were recombinant with an estimated baseline recombination frequency of 2−4 × 10 −5 per base each replication cycle (Froissart et al, 2005). Other studies support these findings of recombination amongst many groups of viruses (Aaziz and Tepfer, 1999;Banner and Lai, 1991;Bruyère et al, 2000;Revers et al, 1996;Rokyta et al, 2006) and viroids (Keese and Symons, 1985;Rezaian, 1990).…”
Section: Type Of Organismmentioning
confidence: 85%
See 1 more Smart Citation
“…Using Cauliflower mosaic virus as a model, over 50% of viral genomes recovered after a single host infection were recombinant with an estimated baseline recombination frequency of 2−4 × 10 −5 per base each replication cycle (Froissart et al, 2005). Other studies support these findings of recombination amongst many groups of viruses (Aaziz and Tepfer, 1999;Banner and Lai, 1991;Bruyère et al, 2000;Revers et al, 1996;Rokyta et al, 2006) and viroids (Keese and Symons, 1985;Rezaian, 1990).…”
Section: Type Of Organismmentioning
confidence: 85%
“…One study that measured the rate of recombination demonstrated frequent HGT between viruses during every infection, higher than the rate of mutations per base (Froissart et al, 2005). Using Cauliflower mosaic virus as a model, over 50% of viral genomes recovered after a single host infection were recombinant with an estimated baseline recombination frequency of 2−4 × 10 −5 per base each replication cycle (Froissart et al, 2005).…”
Section: Type Of Organismmentioning
confidence: 99%
“…However, in spite of the relevant epidemiological role of genetic exchange, till date, little information is available on the rates with which it occurs in plant viruses in the absence of selection. Recombination rates have been experimentally estimated in coinfections of different genotypes of Brome mosaic virus [28,29], Cauliflower mosaic virus (CaMV) [30] and TEV [31]. Although results obtained should be compared with caution, they are similar (particularly those of CaMV and TEV) and as high as mutation rates (at least for TEV), indicating that recombination may be as relevant as mutation in creating variability [31].…”
Section: Generation and Modulation Of Genetic Diversity: Driving Forcmentioning
confidence: 99%
“…Furthermore, to give rise to increased risk, the recombinant virus that acquires a viral transgene should also be more harmful than the parental virus and arise more frequently than background levels of viral HGT. Although recombination events in viruses have sometimes contributed to greater disease burden (Legg and Thresh, 2000), these cases represent only a minute fraction of all HGT events (Froissart et al, 2005).…”
Section: Hgt From Gm Plants To Virusesmentioning
confidence: 99%